A Comparison of Growth Characteristics, Dry Matter Yield, and Forage Quality Between Mixed Cropping and Pure Stand Systems (Monoculture Systems) - Renny Fatmyah Utamy; Herry Sonjaya; Kusumandari Indah Prahesti (Faculty of Animal Science, Universitas Gadjah Mada, 2020)
Smallholders beef cattle are facing many problems, such as the unsustainable supply, limited quantity, and poor quality of forage, which all are crucial to increase the population and productivity of their beef cattle. Therefore, the objective of this study was to evaluate the effects of monoculture and mixed cropping system between dwarf napiergrass with siratro and centro on growth characteristics, fresh and dry matter (DM) yield, and forage quality. The study was carried out for 4 months. There were 3 experiment treatments, namely P0 = dwarf napiergrass (Pennisetum purpureum cv Mott) planted on monoculture system; P1 = dwarf napiergrass planted in mixed cropping system with siratro (Macroptilium atropurpureum cv Siratro); and P2 = dwarf napiergrass planted in mixed cropping system with centro (Centrocema pubescent). All treatments were replicated 3 times. All plants on each treatment were planted on 3 3 m plots, with 1 m of distance between the plots. Data were collected four times after transplanting, i.e. August 20th, September 17th; October 28th; and December 16th of 2017, respectively. The results of study indicated that neither plant height nor tiller number in all treatments and measurement periods were significantly affected (p>0.05), except in month-3 (plant height) and month-4 (tiller number). Although treatments did not alter fresh and DM yield (p>0.05), the DM yield from mixed cropping system tended to be higher. Hence, it can be concluded that growth characteristic, productivity, and forage quality in mixed cropping system were better than in monoculture system.